ANALISIS EFEKTIVITAS DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK KENDARAAN BERMOTOR DI SUMATERA BARAT - Yuskar. , Febri Yanti (Jurnal Riset Akuntansi dan Bisnis, 2014)
Motor vehicle tax is one of local tax that contributed greatly to the revenue of LocalTaxes in West Sumatra. This research aims to analyze the effectiveness and thefactors that influence revenue of motor vehicle tax in West Sumatra . The factorssuspected to affect revenue of motor vehicle tax in West Sumatra are the number ofmotor vehicles , number of population and economic growth . The data used in thisstudy is secondary data 2007-2011 . The results of this study indicate that number ofvehicles and population affect the revenue of motor vehicle tax, whereas economicgrowth does not affect to revenue of Vehicle Tax in West Sumatra . Therefore, DinasPengelola Keungan Daerah (DPKD) can consider the number of vehicles and thenumber of population in setting policy on motor vehicle tax. In addition to increasingthe revenue of the motor vehicle tax, DPKD can improve services in the motorvehicle tax payment process and socialize taxpayer liability.